Cross-cultural effects on drivers' hazard perception : validating a test paradigm for developing countries - Lim, Phui Cheng (2017)
The hazard perception skill of a driver refers to their ability to identify potentially dangerous events on the road, and is one of the only driving-specific skills that has been consistently linked to accident rates. Hazard perception tests are used in several developed countries as part of the driver licensing curriculum, however little research has been done in developing countries where road safety is a primary concern. The extent to which hazard perception skill transfers to different driving environments is also unclear. This thesis therefore has two major aims: to examine hazard perception in a cross-cultural context, and to validate a hazard perception test for potential use in driver licensing in lower-income, developing countries.